Learning strategies in university students of first year of school psychology – UNHEVAL - Coletti Escobar, Gabriel (2009)
The study described learning strategies in university students attending the first year of studies, according to the categories defined in the inventory of skills and learning strategies (IHEA), the research was conducted at a level exploratory and descriptive in a sample 38 students academic career in psychology, ages 17 to 26 years. Results show that 55% of students reached the average of the expected learning strategies, with a regular level. Thus, 24% of them already on a good level of use of learning strategies, and 24% of students are running a bad level, not reaching half the expected learning strategies. Showed higher percentages of students in regular-level learning strategies, including selection of main ideas with 74%, 66% motivation, anxiety and self-61% concentration 53%, information processing and support for the study 50%, with poor levels of learning strategies in time management 45% and a good level of support for the study with 37% of students tested. We conclude that the aspects identified as differentiating the strategies of our students are privileged to explain to some extent by being enrolled in the first year of the race, which places them at the transition between school and university culture.